Gestión de riesgo operativo en la Cooperativa de Ahorro y Crédito Futuro Lamanense del Cantón La Maná, Provincia de Cotopaxi período 2020 - Huilca Semanate, Dayra Guadalupe (2022)
The present work was carried out in the La Maná canton, in the Lamanense Future Savings and Credit Cooperative, the main objective of the research project is to prepare a manual for the management of operational risk, 3 methods were used, inductive, deductive, synthetic with in order to know the present risks and generate decision-making efficiently, as well as the bibliographical research that was the basis for the construction of the theoretical framework, giving solutions to the present problems, through the application of interviews and surveys, for this purpose, It took as a population 10 people who work within the Cooperative including the Manager, it was taken as a study sample due to the population that is very small. Based on the established objectives, financial indicators were applied for operational risk management, measuring the delinquency rate, it is at a low residual risk level with 5% delinquency, this can affect the entity in the long term, by increasing credits. with unpaid interest due to the non-compliance of the partners, to correct this, the application of credit policies and methodologies is proposed, provisional problematic portfolio coverage giving us 17%, which means that the problematic portfolio is on track with delinquency representing a portfolio Medium risk problem, due to the fact that it has a portfolio that does not accrue interest, provision of 77%, which means the higher the provision, the better resources the Cooperative has, to face any obligation that may arise.